Estimasi potensi sumberdaya ikan di perairan Kecamatan Teluk Pandan, Sangatta Selatan, Sangatta Utara dan Bengalon Kabupaten Kutai Timur: The potency estimations of fish resources at Teluk Pandan, South Sangatta, North Sangatta and Bengalon District Waters East Kutai Regency - Juliani (Fakultas Perikanan dan Ilmu Kelautan, Universitas Mulawarman, 2022)
In order to reduce the exploitation of natural resources in the territorial waters of Teluk Pandan, South Sangatta, North Sangatta and Bengalon, the coastal and marine resources should be wisely exploited. It is necessary to study on the potential of fish resources in each region, so that in addition to provide opportunities to pursue economic activity in the capture sector greater, as well as to look for ways to anticipate the negative impacts of coastal and marine resource use such as avoiding physical and biological degradation. Purpose of this study was to determine the status of utilization of fish resources in the 4 districts and its adjacent waters, in order to evaluate and planning, especially about fishing, fish species and management (zoning). Study approach through field surveys and laboratory analysis (ex situ), and approach literature from civil institutions and research results for secondary data. The waters highest productivity in the waters of Teluk Pandan district with the potential density stocks of 59.169 kgs/km2, crustaceans 4,344 kgs/km2 and molluscs 297 kgs/km2, while the most minimal of fish stocks in the area Bengalon District (22.557 kg/km2). But by category mollusk biota to the highest in-stock in Bengalon District waters of 919 kg/km2, followed by South Sangatta 843 kg/km2. Status of fish resources utilization rates in Teluk Pandan District, South Sangatta, North Sangatta, Bengalon and overfishing is not biologically (Underfishing), the results of stock density estimation (total biomass) and the condition of the actual production levels.